Toll-like-receptor-3 function is critical for aortic valve stenosis development in mice. (25th November 2020) - Niepmann, S.T; Boucher, A.S; Bulic, M; Goody, P.R; Jansen, F; Treede, H; Nickenig, G; Zimmer, S
Abstract: Background: Aortic valve stenosis (AS) is the most common valve diseases in the western world. After having been considered a passive degenerative process, which develops as an inevitable consequence of age-related valvular degeneration, basic research of the last two decades has led to a paradigm shift. It is now believed that AS pathophysiology is driven by distinct molecular and cellular mechanisms which include inflammatory pathways. In recent years, Toll-like-receptor-3 (TLR3) has emerged as a major regulator of vascular inflammation. TLR3 is a lysosomal pattern recognition receptor that recognizes single and double stranded RNA. Its activation leads to expression of pro-inflammatory cytokines via NFkb activation. The role of TLR3 in the development of AS has never been investigated. Methods: Severe AS was induced in Wildtype-, ApoE- and TLR3/ApoE−/− mice. For this, a coronary springwire was used to induce an endothelial injury under echocardiographic guidance. Stenosis development was confirmed via ultrasound examinations. To inhibit TLR-3 activation, TLR3/RNA- Complex inhibitor C4a was injected every 48h after wire injury in WT mice. Valves were explanted and stained with hematoxylin/eosin (valve thickening) or anti-68 (macrophage infiltration). Valves from patients who received aortic valve replacement due to AS or aortic regurgitation (AR) were collected and mRNA levels of TLR3 and MyD88 were measured with use of quantitative-PCR. Results: To evaluate weather TLR3 effects AS development in mice, we subjected TLR3/ApoE double- and ApoE knockout mice to our model of wire-induced AS. Surprisingly, TLR3 deficient mice failed to develop AS after wire injury. Peak velocity measurements showed no increase and histological analysis showed lower aortic valve area and macrophage infiltration compared to control mice. In order to pharmacological inhibit TLR3, WT mice were treated with C4a after wire injury. Compared to PBS control, C4a mice also did not develop AS upon wire injury. Trans-aortic valve peak velocity levels were significantly lower in C4a mice. Histological analysis underlined these results and showed thinner aortic valves and decreased macrophage infiltration in C4a mice comparted to control animals. To confirm our hypothesis, the expression of TLR3 and its downstream effector MyD88 were measured in human aortic valve specimens. qPCR analysis revealed decreased TLR3 and MyD88 expression in patients with AS compared to patients with AR. Conclusion: In the presented study, we present first data that theTLR3 has a crucial role in the development of AS in mice. The exact downstream effects after TLR3 activation in AS need to be further investigated. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft (DFG, German Research Foundation)